Determining the correct identity of South African Marthasterias (Echinodermata: Asteroidea). Issue 3 (23rd September 2016) - Wright, AG; Pérez-Portela, R; Griffiths, CL
Abstract : Marthasterias glacialis are found in the cool-temperate waters of the north-eastern Atlantic Ocean, in the subtropical waters of the Mediterranean Sea and along the south-western tip of Africa. The South African Marthasterias population includes two morphotypes, a smooth, spineless rarispina form and a spiny africana form, that have been described as separate species, subspecies, or forma by various authors over the past century. To test whether these two morphotypes represent separate species, and whether either, or both, are conspecific with the North-East Atlantic species, 78 Marthasterias were collected from the Cape Peninsula of South Africa. Morphological comparisons between individuals of the two forms showed no significant clustering of samples, indicating that there is no morphological separation of the two South African forms into distinct groupings. The africana and rarispina forms were also shown to be genetically indistinguishable, using a fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene and the nuclear internal transcribed spacer 1 (ITS1). In addition, the COI sequences were also compared to those from European specimens, and phylogenetic reconstruction and intra- and interspecific levels of divergence suggested that the South African specimens form a single group that is genetically distinct from the European M. glacialis . Although the allopatric distribution, high genetic divergence (more than 3% for the COI fragment) and morphological differences suggest that the South African form should be raised to species status under the name Marthasterias africana, further work must assess an independent genetic marker (nuclear) to support raising the COI clade to species level. True M. glacialis have a spine-armament pattern of a series of three or more regular spine rows down the length of each arm, whereas M. africana are either covered in many irregularly spaced spines, or have an extraordinarily bare surface with only two spine rows per arm. Marthasterias africana may also have an actinal spine simulating the presence of a third inferomarginal spine. This work tentatively resolves the taxonomic dispute, elucidates the separation and amalgamation of the two African forms and suggests a single, uniquely South African Marthasterias species that might be distinct from the north Atlantic M. glacialis, although further analyses to test reproductive isolation between the North-East Atlantic and South African forms are required.